2013
DOI: 10.1177/0218492313495402
|View full text |Cite
|
Sign up to set email alerts
|

Late relapse of multiple myeloma presenting as a right atrial mass

Abstract: Intracardiac involvement is a rare presentation of relapsed multiple myeloma. We present a case of lobulated mass in the wall of the right atrium, with extension to the inferior vena cava and obliteration and encasement of the interatrial septum in a 57-year-old man, a known case of multiple myeloma, with progressive exertional dyspnea and anasarca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…16 There is no clear 1), including surgical resection. 9 In our patient, surgical resection was used to remove a large part of the space-occupying mass, and superior vena cava venoplasty was performed. Short-term follow-up showed that the symptoms of obstruction completely disappeared and TEE showed no signs of recurrence.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…16 There is no clear 1), including surgical resection. 9 In our patient, surgical resection was used to remove a large part of the space-occupying mass, and superior vena cava venoplasty was performed. Short-term follow-up showed that the symptoms of obstruction completely disappeared and TEE showed no signs of recurrence.…”
Section: Discussionmentioning
confidence: 96%
“…We searched for cases of MM with cardiac solid space-occupying lesions reported in the last 10 years on PubMed and only found 11 other cases. [3][4][5][6][7][8][9][10][11] We used a table to list the sex, age, symptoms, disease course, imaging method used for mass diagnosis, site and size of mass, treatment method, and outcome of these patients (including the current case) (Table 1). These 12 patients comprised eight males (67%) and four females (33%), with a mean age of 64. and spread along the endocardium to surrounding tissues; this leads to embolism or obstruction and corresponding clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical symptoms of extramedullary intracardiac MM are nonspecific, depending on the localization and size of the mass. Patients might present with pericardial tamponade, arrhythmia, SVC syndrome, or severe heart failure [ 5 , 10 ]. In this case, the large right atrial mass resulted in symptoms of SVC obstruction and right heart dysfunction in the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical intervention is usually palliative because the intracardiac plasmacytoma usually infiltrates the myocardium and cannot be removed entirely. However, surgical intervention could immediately improve hemodynamics [ 10 , 13 ]. Our patient differed from the previous patients who received surgical intervention for intracardiac plasmacytomas in one crucial aspect.…”
Section: Discussionmentioning
confidence: 99%